Where eagles dare - Burton, Richard 1925-1984; Eastwood, Clint 1930-; Ure, Mary 1933-1975; Wymark, Patrick; Hordern, Michael (Clint Eastwood collection)
An American general is shot down over Germany during WWII and captured. Unknown to the Germans, he has full knowledge of the D-Day operation. British Intelligence puts together a team to rescue him, but an American is in the squad for reasons unknown.